Pengaruh Rasio Likuiditas dan Rasio Solvabilitas terhadap Kinerja Keuangan Perusahaan Manufaktur (Sektor Makanan dan Minuman) yang Terdaftar di BEI pada Tahun 2022-2023 - Ether, Christian; Pranata, Aja; Jaya, Akmal Atma; Manurung, Alicia Veronica; Purba, Christyne Lourenza; Silaban, Citra Zueta; Noor, Durratul Farrah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study examines the impact of liquidity and solvency ratios on the financial performance of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2022-2023 period. Amid global economic challenges, maintaining financial stability is crucial for the sustainability of business operations. The research employs secondary data from the financial statements of selected companies using a quantitative approach. The results indicate that, simultaneously, the Current Ratio (CR) and Debt-to-Equity Ratio (DER) significantly affect the Return on Assets (ROA). Higher liquidity ratios tend to improve financial performance, while solvency ratios play a vital role in determining a company's financial health. This study emphasizes the importance of financial statements as a tool for evaluating company performance and supporting strategic decision-making.